Are We Having Fun Yet? Children’s Adult-Organized Recreational Basketball as a Site of Discipline - Gracey, Bonita (Ethnologies, 2010)
This paper examines children’s adult-organized recreational sport through the lens of Foucauldian disciplinary technologies. Despite decades of effort and changes to children’s sport, there is still difficulty in meeting the needs of many of the participants. This article argues that it is time to seriously reconsider the dominating role that adults occupy in children’s sport and that we need to find ways to give more of the control of sport to the participants.